The Value of Media in the Acquisition of Master Degree Program: Students’ Assessment - Černova, Emīlija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Rapid development of innovative processes characterizes the conditions of the scientific and technical revolution. The understanding about the place and role of the man in the innovative society also changes. Therefore the readiness of the social and individual consciousness to changes in all spheres of life (including education) and the acceptance of the novelties as a value are important. It testifies about a new orientation of education which applies to methods as well as their forms, content and aim. But is the preschool teacher ready to use media in her professional work? Does the acquisition of higher education promote it? The aim of the article is to study the use of the innovative teaching/learning activities in the acquisition of the Master degree program.